ANALISIS KEMAMPUAN LITERASI MATEMATIS PESERTA DIDIK MTS NEGERI DI KOTA BIMA - Rahman, Zahra Fadhila; Suryadi, Didi; Nurjanah, Nurjanah (Universitas Batanghari Jambi, 2024)
Mathematical literacy skills are important to answer various problems systematically by using facts and information. This skill is important to have, especially for students. With this skill, students will be able to face today's increasingly complex developments. This research discusses the mathematical literacy skills of class VII students at one of the MTsN in Bima, West Nusa Tenggara. This research uses a descriptive qualitative approach. Data was collected through a written test with four essay questions on the material